BRIDGING THE GAP EBIII-IBA: EARLY INTERMEDIATE BRONZE RADIOCARBON DATES FROM KHIRBAT EL-'ALYA NORTHEAST, ISRAEL. Issue 6 (18th December 2020) - Lev, Ron; Shalev, Omer; Regev, Johanna; Paz, Yitzhak; Boaretto, Elisabetta
ABSTRACT: Recent radiocarbon ( 14 C) research demonstrates that the urban culture of Early-Bronze III in the southern Levant ends around 2500 BC, and not around 2300 BC as was widely assumed. This should extend the Intermediate Bronze Age by 200 years. Charred olive pits from Intermediate Bronze Age contexts in the site of Khirbat el-'Alya Northeast in the Judean Shephelah region (Israel) were 14 C dated, resulting in calibrated dates around 2500 BC. The date range of Khirbat el-'Alya Northeast samples is an indication that in the Mediterranean parts of the southern Levant, the Intermediate Bronze Age material culture appeared around the time of the decline of the preceding culture of Early-Bronze III—around 2500 BC or somewhat earlier. Possible Intermediate Bronze settlement pattern and the site's relation to the nearby Early-Bronze city of Tel Yarmuth are discussed based on previous Intermediate Bronze and Early-Bronze related research in the surrounding area.